Integrating X-Ray Computed Tomography With Chemical Imaging to Quantify Mineral Re-crystallization From Granulite to Eclogite Metamorphism in the Western Italian Alps (Sesia-Lanzo Zone) - Corti, Luca; Zucali, Michele; Visalli, Roberto; Mancini, Lucia; Sayab, Mohammad (Frontiers in Earth Science, 2019)
Metamorphic transformations and fabric evolution are the consequence of thermo-dynamic processes, lasting from thousands to millions of years. Relative mineral percentages, their grain size distribution, grain orientation, and grain boundary geometries are first-order parameters for dynamic modeling of metamorphic processes. To quantify these parameters, we propose a multidisciplinary approach integrating X-ray computed microtomography (µ-CT) with X-ray chemical mapping obtained from an Electron MicroProbe Analyzer (EMPA). We used a metapelitic granulite sample collected from the Alpine HP-LT metamorphic rocks of the Mt. Mucrone (Eclogitic Micaschists Complex, Sesia-Lanzo Zone, Western Alps, Italy). The heterogeneous Alpine deformation and metamorphism allowed the preservation of pre-Alpine structural and mineralogical features developed under granulite-facies conditions. The inferred granulitic mineral association is Grt + Bt + Sil + Pl + Qtz ± Ilm ± Kfs ± Wm. The subsequent pervasive static eclogite-facies re-equilibration occurred during the Alpine evolution. The inferred alpine mineral association is Wm + Omp ± Ky + Qtz+ Grt though local differences may occur, strongly controlled by chemistry of microdomains. X-ray µ-CT data extracted from on centimeter-sized samples have been analyzed to quantify the volumetric percentage and shape preferred orientation for each mineral phase. By combining tomographic phase separation with chemical variation and microstructures (i.e., different grain-size classes for the same phase and morphology of different pre-Alpine microdomains) the pre-Alpine mineralogical phases from the Alpine overprint have been distinguished and quantified. Moreover, the sample preserves 100% of the pre-Alpine granulite fabric, which surprisingly corresponds to less than 22% of the corresponding pre-Alpine metamorphic assemblages, while the Alpine eclogitic static assemblage corresponds to 78% though no new fabric is developed. This contribution demonstrates that the combined use of EMPA X-ray chemical mapping with the X-ray µ-CT shape analysis permits a dynamic approach to constrain the chemistry of the mineral phases linked to the development of metamorphic-related static and dynamic fabrics.